2013
DOI: 10.1002/tesj.89
|View full text |Cite
|
Sign up to set email alerts
|

Adult ESOL Students and Service‐Learning: Voices, Experiences, and Perspectives

Abstract: This multiple‐case study examined the unique perspectives of six adult English for speakers of other languages (ESOL) students who participated as the givers of a service in a semester‐long service learning community college ESOL course. Their ages ranged from 19 to 45 and they hailed from five different countries (Colombia, Mexico, South Korea, Venezuela, and Vietnam). This study focused on the students' perspectives regarding their oral communication skills, and specific examples have been drawn from sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…One of the most salient teacher identities that students constructed throughout the semester was teachers as advocates for social justice. This corresponds to the literature that service‐learning can provide culturally rich experiences for prospective teachers to learn to walk the road of social justice (Bippus & Eslami, ; Boyle‐Baise, ; Cipolle, ; Endres & Gould, ; Farnsworth, ; Moore, ; Ruppert, ; Tinkler, Lynne, Tinkler, & Miller, ). Critical reflection on service‐learning can assist future and current teachers in uncovering the inequities that many ELLs encounter in school and in society, laying the groundwork for social justice and equity (Cipolle, ).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…One of the most salient teacher identities that students constructed throughout the semester was teachers as advocates for social justice. This corresponds to the literature that service‐learning can provide culturally rich experiences for prospective teachers to learn to walk the road of social justice (Bippus & Eslami, ; Boyle‐Baise, ; Cipolle, ; Endres & Gould, ; Farnsworth, ; Moore, ; Ruppert, ; Tinkler, Lynne, Tinkler, & Miller, ). Critical reflection on service‐learning can assist future and current teachers in uncovering the inequities that many ELLs encounter in school and in society, laying the groundwork for social justice and equity (Cipolle, ).…”
Section: Resultssupporting
confidence: 76%
“…() argue that students and the community members mutually benefited from service‐learning by creating the opportunity for authentic relationship building between participants while teaching English to Karen refugees. Bippus and Eslami () demonstrate how adult ESL students gained self‐confidence and became more active language learners by taking service‐learning courses at a community college.…”
Section: Why Service‐learning?mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, they looked for transformative learning experiences, academic language learning, autonomy, and intercultural preparedness. Service learning for postsecondary EAL students in the United States also seemed to garner appreciation for active learning, an authentic environment, and confidence boosting (Bippus & Eslami, 2013). Perren (2013) concluded that service learning as part of a university intensive English course promoted community building and personal growth opportunities.…”
mentioning
confidence: 99%
“…In the introduction to that special issue, Adrian Wurr () noted that “although service‐learning in TESOL is in the early stages of development compared to other disciplines … research on service‐learning in TESOL is maturing rapidly” (p. 397). Recent scholarship has examined service‐learning in undergraduate ESL‐specific courses (e.g., Askildson, Kelly, & Mick, ; Bippus & Eslami, ; Elwell & Bean, ; Heuser, ; Minor, ; Perren, Grove, & Thornton, ; Wurr, , 2009), service‐learning and preservice TESOL teachers (e.g., Kassabgy & Salah El‐Din, ; Moore, ; Rueckert, ; Smolen, Zhang, & Detwiler, ), and service‐learning and ESL graduate students (Crossman & Kite, ).…”
mentioning
confidence: 99%